Fresno-Merced Counties Legal Services Staff - Watkins, Howard::::::::: (1985)
Lunch meeting with Marc Feldman, Howard Watkins, Chris Marie Brown, Michael Kanz, Bob Higgins and Jose Garay at Yturri Hotel